Design of a modified natural egyptian solar house - Hanaa M. Farghally; Faten H. Fahmy; Amal A. Hassan; Ninet M. Ahmed (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The rate of increase in energy consumption and high costs in addition to the depletion of existing resources has a significant impact on our standard of living for next generations. In this case, the priority is to develop alternative cost-effective sources for powering the residential and non-residential buildings. This paper proposes and develops a design of a modified small two-story residential solar house for a medium-sized family located in Cairo, Egypt. This modified solar house meets almost all its energy demands including space heating by using solar air collector with a pebble storage unit in winter and a summer cooling system using wind catcher theory. Hot water is obtained throughout the day by using a steel sheltered water storage tank with a capacity of 1000 liter. Finally, the proposed heating system of the solar house is sized and modeled.